Emotional Marketing To Purchase Decisions Halal Food In Medan City With Brand Awareness As Variable Intervening - Elfitra Desy Surya; Megasari Gusandra Saragih (AIBPM Publisher, 2019)
Emotional Marketing is a new concept in the Marketing world with the aim of giving a unique impression by highlighting the emotional side of a brand and halal food products. The purpose of this research is to analyse how emotional marketing affects Purchase Intention through brand awareness. The object to be researched on this research is food products halal. The samples in this study amounted to 100 respondents, namely the society that was a substitute for halal food. The sampling techniques in this study used the insidentalsampling technique. The type of data collection in this study uses the distribution of the questionnaire to the research sample. The results proved that emotional marketing done for halal food has a direct influence on brand awareness and purchase intention